ETIKA ISLAM DALAM TAJUSSALATIN KARYA BUKHARI AL-JAUHARI - Hadi W. M., Abdul (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
AbstractThe book of Tajussalatin is an ethics book. The book is a synthesis of scientific, philosophical and literature essay. Thesubstance of the book is a concept of state power in Islam and how to govern a state. Bukhari explains the concept from âTasawufâ point of view where the state cannot be described as an individual power of a king, but it is a governmental organization bases on Islamic laws. According to Islamic laws, a king is one level with others. They are representatives of God on the earth and also God servants with each capacities. Thus, the ideal state according Bukhari is the law state bases on Islamic political ethics which is Islamic laws. Therefore, the state needs an institution of justice (qadhi) which has a role in maintaining the state law. According to him, the justice is nothing and non-sense if it is not based on the law which is deeply obeyed by all people.Keywords: Islamic ethics, Tajussalatin, Bukhari al-Jauhari, statepower.